Devising methodological provisions for the comparative evaluation of variants for an armament sample in terms of military-technical level - Zahorka, Aleks; Shchypanskyi, Pavlo; Pavlikovskyi, Anatolii; Koretskyi, Andrii; Bychenkov, Vasyl (Eastern-European Journal of Enterprise Technologies, 2019)
When setting a tactical-technical task on constructing a sample of armament, not only its characteristics related to purpose are considered, but its operational and technical, technological, economic, and other characteristics as well. The totality of characteristics defines the military-technical level of the armament sample. Typically, such variants of armament sample are considered that differ by the set of characteristics. For comparative estimation of armament sample variants in terms of military-technical level, it is necessary to apply appropriate methodical provisions. Resolving the task on comparative evaluation of armament sample options was made possible by consistently solving four problems. In solving the first problem, the decomposition of the totality of characteristics of an armament sample into the following three levels has been performed: properties, properties' components, indicators. The scientific result from the first problem is a methodological approach to comparative evaluation of armament sample options based on the consideration of the characteristics' significance when ranking the variants of an armament sample using a method of multi-criteria analysis. Solving the second problem helped establish the order of staged expert estimation of coefficients for the properties' significance, properties' components, and indicators, using a pairwise comparison method, which makes it possible to take into consideration their impact on the military-technical level of an armament sample. The result from solving the third problem of the current study is the algorithm for comparative evaluation of an armament sample using a taxonomy method. The reported algorithm makes it possible to rank the variants of an armament sample taking into consideration the significance of indicators that define their military-technical level. Our decomposition of characteristics, using a pairwise comparison method for expert estimation of their significance, as well as a taxonomy method, has made it possible to obtain an integrated procedure for the comparative evaluation of an armament sample variants in terms of the military-technical level. When solving the fourth task of this study, we have considered the order of application of the devised procedure using an example of comparative estimation of the military-technical level of variants for an anti-aircraft missile system. The methodology could be used in substantiating a tactical-technical task on the development of armament samples.